Analysis of Topography and Composition of the Von Kármán Impact Crater. Issue 1 (February 2021) - Hou, Jinlong; Li, Li; Li, Shiwei
Abstract: The Vo n Kármán impact crater in the Chang'E-4 landing area is located in in the Northwestern South Pole-Aitken (SPA) basin on the back of the Moon, and the analysis of its topography and compositional characteristics is essential for the landing of the probe and the exploration of the lunar surface, which plays a fundamental role in obtaining information on the geomorphology and geology of the lunar surface. In this paper, the topography of the Vo n Kármán impact crater is analyzed based on DEM, slope and terrain roughness, then the compositional characteristics of the Von Kármán impact crater are analyzed according to TiO2 and FeO content through combining LRO LOLA data and Clementine UV-VIS data. This study is a basis for revealing the surface characteristics and structure of the Moon.